Resistance and the Struggle for Access: The Wadas Women's Movement Against Ecological Injustice in National Strategic Projects - Erlangga, Gustian Aditya; Fadli, Yusuf; Hermawan, Dharma; Isbandi, Fitri Susiswani (JED (Jurnal Etika Demokrasi), 2024)
This study examines the ecological injustice experienced by women in Wadas Village as a result of the National Strategic Project involving andesite mining for the construction of the Bener Dam in Central Java, Indonesia. It aims to evaluate the critical role of women in combating environmental degradation while advocating for gender equality and sustainable development. Employing a descriptive qualitative approach, the research utilizes data sourced from scientific articles, online media, and legal documents. The findings reveal that the Wadon Wadas movement, spearheaded by women, has effectively resisted repression and navigated legal challenges through various forms of protest and legal action, highlighting community resilience and a commitment to environmental conservation. The study concludes that women's movements can effectively challenge state policies that jeopardize ecological and social well-being, with the potential to influence public policy and safeguard natural resources.